Answer:
x= -1
y = 9
Explanation:
to solve this system of equation
let
x - 2y = -19.....................................equation 1
-3x + 5y = 48 .................................. equation2
from equation 1
x - 2y = -19.....................................equation 1
x = -19 + 2y................................... equation 3
substitute the value of x into equation 2
-3x + 5y = 48 .................................. equation2
-3(-19 + 2y) + 5y = 48
57 - 6y + 5y = 48
combine the like terms
-6y + 5y = 48 -57
-y = - 9
divide both side by -
y = 9
put y= 9 into equation 3
x = -19 + 2y................................... equation 3
x = -19 + 2(9)
x = -19 + 18
x = -1
therefore the value of x and y is -1 and 9 respectively